Profile of informal sector workers and factors affecting informal sector employment in Jambi Province - Purwaka Hari Prihanto; Adi Bhakti (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
This study aims to analyze; 1) the profile of informal sector workers in Jambi Province; 2) The development of informal sector employment in Jambi Province; 3). the effect of economic growth, population, and income per capita on informal sector employment. The data used microdata of National Labor Force Survey, Jambi Province 2015. The results showed; 1) Informal sector workers in Jambi Province 81.5 percent are in rural areas, dominated by male workers, mostly poorly educated, and work in agriculture; 2). During the period 2005-2015, the average growth of the informal sector was 1.3 percent per year, and 3) Simultaneously the economic growth, population, and income per capita had a significant effect on informal sector employment.Keywords: informal sector, economic growth, population, and income per capita